2015
DOI: 10.1016/j.cortex.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating the aberrant brain: Evidence for increased cortical hyperexcitability from a transcranial direct current stimulation (tDCS) study of individuals predisposed to anomalous perceptions

Abstract: Findings from neurological and clinical groups have shown that increased predisposition to anomalous experience/aura reflects an elevation in aberrant neural processes in the brain. However, studies of anomalous experiences in non-clinical/non-neurological groups are less clear on this matter and are more typically confined to subjective questionnaire measures alone. The current investigation, the first to our knowledge, carried out a transcranial Direct Current Stimulation (tDCS) study of cortical hyperexcita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
(134 reference statements)
1
9
0
Order By: Relevance
“…In addition, the Cronbach's alpha (> .80) suggested that the responses to these items were highly consistent with each otheran observation further bolstered by the near perfect replication of the original study for this factor. Pattern and light induced visual stress symptoms (which can include induced somatic discomforts) are consistent with the notion of elevated hyperexcitability in visual cortex and have been well documented in studies on migraine and non-clinical samples predisposed to aberrant perceptions and hallucinations Braithwaite, Mevorach, & Takahashi., 2015;Harle, Shepherd, & Evans, 2006;Huang et al, 2003;Wilkins, 1995).…”
Section: The Factor Structure Of Chi-ii Factor 1 -Heightened Visual Ssupporting
confidence: 71%
“…In addition, the Cronbach's alpha (> .80) suggested that the responses to these items were highly consistent with each otheran observation further bolstered by the near perfect replication of the original study for this factor. Pattern and light induced visual stress symptoms (which can include induced somatic discomforts) are consistent with the notion of elevated hyperexcitability in visual cortex and have been well documented in studies on migraine and non-clinical samples predisposed to aberrant perceptions and hallucinations Braithwaite, Mevorach, & Takahashi., 2015;Harle, Shepherd, & Evans, 2006;Huang et al, 2003;Wilkins, 1995).…”
Section: The Factor Structure Of Chi-ii Factor 1 -Heightened Visual Ssupporting
confidence: 71%
“…Further support for this position comes from subsequent work which showed that in a group of clinically healthy student volunteers, participants who experienced increased pattern-glare showed increased response to cortical excitation, delivered via anodal tDCS stimulation and decreased response to cortical inhibition delivered via cathodal stimulation (Braithwaite, Mevorach, & Takahashi, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The fact that PRVS is more likely to be evoked under binocular than monocular conditions also supports this view [ 12 ]. Unlike the natural images that cause a sparse response in the visual system, visually averse stimuli may cause an anomalous response as found in PRVS, as a result of either cortical hyperexcitability or poor cortical inhibition [ 5 , 13 16 ]. Previous studies suggested an overload in extrastriate dorsal visual pathway in PRVS [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cortical hyperexcitability has also been reported in the visual cortex of the people with migraines [ 28 , 29 ]. Therefore, PRVS and migraine should be viewed as the two ends of a continuum, with PRVS in the non-clinical population who experience abnormal illusions and migraine in the clinical population who suffer migraine attacks [ 16 ].…”
Section: Introductionmentioning
confidence: 99%